Immunologic and Virologic Responses to Nevirapine Based Antiretroviral Therapy (ART) Among HIV-Tuberculosis Co-Infected Ugandan Children on Rifampicin Based Anti-Tubercular Treatment - Moreen Kamateeka; L. Barlow-Mosha; M. Mubiru; M. Lutajumwa; P. Mudiope; P. M. Musoke (HIV/AIDS Research and Treatment-Open Journal, 2015)
Background: Children co-infected with Human Immunodeficiency Virus (HIV) and Tuberculosis (TB) require concurrent treatment with anti-tuberculosis drugs and Antiretroviral therapy (ART). Drug interaction between nevirapine and rifampicin leads to decreased nevirapine levels. The impact of this drug-drug interaction on virologic and immunologic outcomes in the treatment of HIV - TB co-infected children has not been fully studied. A retrospective analysis was conducted to compare the response to nevirapine-based ART regimen among HIV- infected Ugandan children on a rifampicin containing anti-TB regimen for TB disease versus those only on ART. Methods: We analyzed data from HIV infected children aged 6 months to 12 years attending a Paediatric HIV clinic in Kampala, Uganda who between October 2004-June 2006 were enrolled into an ART program based on the 2002 World Health Organization (WHO) ART guide lines for Resource Limited Settings. In this retrospective analysis, children were divided into two groups; those on nevirapine based ART and rifampicin containing anti-TB treatment (TB group) and those on ART alone (no TB group). CD4 cell percent and viral load data obtained at baseline and thereafter 12 weekly until 48 weeks was compared using Wilcoxon rank sum test. Kaplan Meir plots were used to compare virologic success between the two groups over the 48 week follow up period. Results: The analysis included a total of 127 children of whom 20% (26/127) were in the TB group. Median log10 HIV RNA (Interquatile range-IQR) at baseline was 5.69 (5.19-6.19) in the TB group versus 5.59 (4.86-6.32) in the no TB group; p=0.576. Median viral load was undetectable for all children by 12 weeks post ART initiation and this was sustained through 48 weeks irrespective of receiving rifampicin. Baseline median CD4% was not significantly different between the two groups. The median CD4% (IQR) during follow- up for the TB group versus the no TB group was: 17.0 (8.0-26) versus 20.9 (8.0- 33.8), p=0.147 by 12 weeks; 26.0 (12.7-39.3) versus 22.9 (7.5-38.3), p=0.472 by 24 weeks; 26.6 (13.6-39.6) versus 26.4 (12.3 40.5), p=0.927 by 36 weeks and 29.0 (20.0-38) versus 28.9 (16.8-41), p=0.931 by 48 weeks respectively. Conclusion: HIV/TB co-infected children receiving rifampicin demonstrated satisfactory immunologic and virologic responses to nevirapine based ART, similar to children not on anti- TB treatment. These findings provide evidence that nevirapine based ART may remain effective among HIV positive children co-infected with TB who receiverifampicin-based anti-TB treatment.